PETUALANGAN ILMU SOSIAL: PENERAPAN TREASURE HUNT BERBASIS CULTURALLY RESPONSIVE TEACHING UNTUK MENINGKATKAN PARTISIPASI BELAJAR SISWA - Nadziru, Miftakhul Umi; Purnomo, Agus (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
Social studies learning in grade 7 Utsman SMPIT Insan Permata Malang still shows low learning participation caused by the use of conventional learning methods and limited learning media so that students are less actively involved in the learning process. This study aims to increase student learning participation in Social Studies (IPS) subjects through the application of the Culturally Responsive Teaching (CRT) based Treasure Hunt learning method. This study uses a descriptive quantitative approach with a pre-experimental type one group pretest-posttest design, involving 20 students. Research data were collected through learning participation questionnaires, observations of student involvement in learning, and field notes. The results of the study showed a significant increase in the level of student learning participation after the application of the Treasure Hunt method and the results of observation activities showed that students were more active, enthusiastic, and involved in social studies learning activities, especially when the material was linked to the local culture of the Malang region. The CRT approach has been proven to be able to increase student involvement in learning and the Treasure Hunt method is able to create a collaborative, challenging learning atmosphere and encourage intensive interaction between students. ABSTRAKPembelajaran IPS di kelas 7 Utsman SMPIT Insan Permata Malang, masih menunjukkan rendahnya partisipasi belajar yang disebabkan oleh penggunaan metode pembelajaran konvensional serta keterbatasan media pembelajaran sehingga siswa kurang terlibat secara aktif dalam proses belajar. Penelitian ini bertujuan untuk meningkatkan partisipasi belajar siswa dalam mata pelajaran Ilmu Pengetahuan Sosial (IPS) melalui penerapan metode pembelajaran Treasure Hunt berbasis Culturally Responsive Teaching (CRT). Penelitian ini menggunakan pendekatan kuantitatif deskriptif dengan desain pre-experimental type one group pretest-posttest, melibatkan 20 siswa. Data penelitian dikumpulkan melalui angket partisipasi belajar, observasi keterlibatan siswa dalam pembelajaran, dan catatan lapangan. Hasil penelitian menunjukkan adanya peningkatan signifikan pada tingkat partisipasi belajar siswa setelah penerapan metode Treasure Hunt dan dari hasil kegiatan observasi menunjukkan bahwa siswa lebih aktif, antusias, dan terlibat dalam kegiatan pembelajaran IPS terutama saat materi dikaitkan dengan budaya lokal wilayah Malang. Pendekatan CRT terbukti mampu meningkatkan keterlibatan siswa dalam pembelajaran dan metode Treasure Hunt mampu menciptakan suasana belajar yang kolaboratif, menantang dan mendorong interaksi antarsiswa secara intensif.